“I am Wolf, I Rule!” - Attributing Intentions to Animals in Human-Wildlife Interactions - Jürgens, Uta Maria (Frontiers in Conservation Science, 2022)
Human interactions with potentially problematic wildlife spawn intense and polarized sentiments. This study investigates one contributing factor: People perceive wildlife as having intentions toward them, and consequently, they feel targeted by the animals' behavior. Thematic analysis of semi-structured interviews with 20 German-speaking participants on three model wildlife – wolves, corvids, and spiders – yielded 12 different kinds of intentions attributed to the animals. The form of these intentions can be analyzed in terms of whether the attribution has a metaphoric or literal meaning; whether it is potentially correct, and whether it occurs at an individual or species level. In terms of these criteria, attributions made to wolves, corvids, and spiders take different forms, that appear to correspond to differential degrees of direct experience with the respective animals. For example, attributions to wolves tend to be made at a species-level, and thus are of a rather abstract quality, corresponding to the rather elusive nature of wolf presence. Simultaneously, attributions to the three model wildlife exhibit thematic similarities: With regard to their content, the 12 kinds of intentions can be integrated into four motives referring to the animals' alleged deeper incentives: rebellion, menace, relationality, and unintentionality. These motives are ascribed to wolves, corvids and spiders in comparable ways, evidencing similarities in participants' mental representations of ecologically dissimilar cases of human-wildlife interactions. The discussion of the qualitative findings traces how the species-specific and the overarching dynamics, as well as people's biographies factor into their views of animal intentionality in a way that causes ascriptions to be polarized across people, yet similar across wildlife. Evidently, the inclination to feel personally targeted by animal agents' intentional behavior is a universal feature in human-wildlife conflicts, that is co-determined by wildlife ecology and human psychology.